Dragon kiss - Baker, E. D. (New York : Bloomsbury, 2009)
Despite obstacles, an ice dragon named Audun pursues the love of his life--a human girl who can transform into a dragon using magic.
Horn Book, April 2010.
6.0
3-6
920L
U
Keywords: Dragons -- Juvenile fiction; Courtship -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Magic -- Juvenile fiction; Fairy tales; Dragons -- Fiction; Courtship -- Fiction; Human-animal relationships -- Fiction; Magic -- Fiction; Humorous stories; Fairy tales; Dragons -- Fiction; Courtship -- Fiction; Human-animal relationship -- Fiction; Magic -- Fiction; Love stories; Humorous fiction; Fairy tales; Love -- Fiction; Human-animal relationships -- Fiction; Magic -- Fiction; Humorous stories; Love stories; Humorous fiction